Yeast cell wall derivatives as a potential strategy for modulating oral microbiota and dental plaque biofilm - Scheithauer, Torsten P. M.; Fernandes de Oliveira, Isabela M.; Ossendrijver, Michel; Dehay, Elodie; van der Wurff, Michelle; Rahaoui, Hakim; Ballet, Nathalie; Keijser, Bart J. F. (Frontiers in Oral Health, 2025)
IntroductionDerivatives from Saccharomyces cerevisiae yeast including yeast extracts and yeast cell walls are sustainable sources of valuable nutrients, including dietary fibers and proteins. Previous studies have shown that certain components from these yeast derivatives can inhibit the growth of harmful intestinal bacteria and promote the growth of beneficial bacteria. However, the effects of yeast derivatives on oral health have not yet been investigated.MethodsAn in vitro oral biofilm model was employed to examine the impacts of yeast derivatives on the oral microbiota and their potential benefits for maintaining oral homeostasis. The model incorporated dental plaque donor material from both healthy and periodontitis diagnosed individuals. Biofilm formation, density, and microbial composition were quantified. Additionally, the production of short-chain fatty acids in the biofilm supernatants was measured.ResultsYeast extracts had only minor effects on oral biofilm formation. In contrast, yeast cell wall derivatives, which are rich in polysaccharides such as beta-glucans and mannans, significantly reduced the density of the oral biofilms in vitro. This reduction in biofilm density was associated with an overall shift in the bacterial community composition, including an increase in beneficial bacteria and a decrease in the abundance of Tannerella forsythia, an important species involved in bacterial coaggregation and the development and maturation of the oral biofilm. Furthermore, the yeast cell wall derivatives decreased the production of short-chain fatty acids, including acetic and butyric acid. These findings were consistent across both healthy and periodontitis microbiomes.ConclusionThis study has demonstrated the potential of yeast cell wall derivatives to positively impact oral health by significantly reducing biofilm density, modulating the oral microbial composition, and decreasing the production of short-chain fatty acids. The observed effects highlight the promising applications of these yeast-based compounds as an approach to managing oral diseases. Further research is needed to fully elucidate the mechanisms of action and explore the clinical potential of yeast cell wall derivatives in promoting and maintaining oral health.